2017
DOI: 10.1136/archdischild-2016-311374
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of in-utero exposures: potential effects of paracetamol on male reproductive development

Abstract: Human male reproductive disorders (cryptorchidism, hypospadias, testicular cancer and low sperm counts) are common and some may be increasing in incidence worldwide. These associated disorders can arise from subnormal testosterone production during fetal life. This has resulted in a focus on in-utero environmental influences that may result in reproductive effects on the offspring in later life. Over recent years, there has been a dramatic increase in the scientific literature describing associations between i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…18 This was supported by Sharpe and Skakkebaek,19 who subsequently proposed that hypospadias, cryptorchidism, poor semen quality, and testicular cancer are symptoms of one underlying entity with a common fetal origin. 20,21 Although an increasing number of studies of maternal lifestyle and health during pregnancy, such as maternal diet, alcohol consumption, smoking, medication use, and obesity support this fetal programming hypothesis, [22][23][24][25][26][27] large-scale epidemiological evidence is still lackingespecially regarding maternal exposure to endocrine disrupting chemicals at home and at work. 28 The limited body of evidence is likely explained by the complex logistics and high costs of establishing long-term longitudinal populationbased studies of male reproductive function, with information on exposures during early life, such as the need for detailed maternal information and bio-specimens stored for decades before follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…18 This was supported by Sharpe and Skakkebaek,19 who subsequently proposed that hypospadias, cryptorchidism, poor semen quality, and testicular cancer are symptoms of one underlying entity with a common fetal origin. 20,21 Although an increasing number of studies of maternal lifestyle and health during pregnancy, such as maternal diet, alcohol consumption, smoking, medication use, and obesity support this fetal programming hypothesis, [22][23][24][25][26][27] large-scale epidemiological evidence is still lackingespecially regarding maternal exposure to endocrine disrupting chemicals at home and at work. 28 The limited body of evidence is likely explained by the complex logistics and high costs of establishing long-term longitudinal populationbased studies of male reproductive function, with information on exposures during early life, such as the need for detailed maternal information and bio-specimens stored for decades before follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…analgesics, metformin and diethylstilboestrol) and lifestyle factors (e.g. diet, alcohol and smoking) (Habert et al , 2014; Kilcoyne and Mitchell, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the exposures used for these studies may not reflect the levels of exposure that are directly relevant to humans. Assessment of experimental studies using experimental animal models must take account of the variations in model systems ( in-vitro versus in-vivo ), exposure regimen and drug metabolism, whilst also accounting for the impact of species differences for each of these parameters (Kilcoyne and Mitchell, 2017). As a result, animal studies often report findings based on relative exposures which exceed human-relevant exposures, often by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…All said, the subject is far from settled, stated the authors of a recent review of prenatal acetaminophen exposures and male reproductive effects. “It cannot be concluded that exposure to paracetamol is a direct cause of male reproductive disorders,” they wrote, “nor that analgesics should simply be avoided during pregnancy.” 19 …”
Section: Finding Fetal Impactsmentioning
confidence: 99%